Aesthetics - Poetics - Art - Haman, Ales (Bohemica Olomucensia, 2018)
This study explores a disposition of aesthetics and its relation with the work of art, mainly the literary one. The author raises the question whether an aesthetical function is the only one, which determines the quality of the artwork, or not. Taking an example of thinking of J. P. Sartre and others, the study shows how much this reductive perception limits an existential understanding of a range of art experience, an experience of contact with artwork. It becomes apparent that specific character of artwork is formed by the aesthetical part as well as by poetical part, which gives concrete shape to the artwork and emphasizes artistic intention itself. This critique of single-minded perception of artwork and its replacing by wider one could lead to separation of structural literary theory as a system of artistic standards from poetical and aesthetical qualities of artwork, which wouldn't be subordinate to semiotic theory. A shift from Saussure-esque concept of artwork as a linguistic sign towards the functional, anthropological concept of art could be a result, too.
Keywords: artificiality of art; aesthetics; poetics; kitsch